2013
DOI: 10.1111/sed.12023
|View full text |Cite
|
Sign up to set email alerts
|

Controls on microbial activity and tidal flat evolution in Shark Bay, Western Australia

Abstract: Microbial deposits at Shark Bay constitute a diverse living microbial carbonate system, developed in a semi-arid, highly evaporative marine setting. Three tidal flats located in different embayments within the World Heritage area were investigated in order to compare microbial deposits and their Holocene evolution. The stressing conditions in the intertidal-subtidal environment have produced a microbial ecosystem that is trapping, binding and biologically inducing CaCO 3 precipitation, producing laminated stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 40 publications
1
82
0
Order By: Relevance
“…Hamelin Pool in Western Australia spans an area of 1220 km 2 with an average tidal range of~60 cm and is well protected by carbonate banks, which confine sea water inflow. In addition, Nilemah contains some of the most well-developed microbial sedimentary systems in Shark bay (Jahnert et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamelin Pool in Western Australia spans an area of 1220 km 2 with an average tidal range of~60 cm and is well protected by carbonate banks, which confine sea water inflow. In addition, Nilemah contains some of the most well-developed microbial sedimentary systems in Shark bay (Jahnert et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Shark Bay offers a more extreme modern analogue, as it is hypersaline (460 psu salinity) compared with Highbourne Cay that has standard marine salinity (33 to 35 psu) Burns et al, 2004). Shark Bay in Western Australia harbours modern analogues consisting of several morphotypes, including lithifying and non-lithifying microbial mats (smooth and pustular, respectively), and mature columnar stromatolites Jahnert et al, 2013). Previous polyphasic approaches combining bacterial culture-dependent and independent approaches by our group and others reported a high diversity of bacterial and haloarchaeal OTUs in Shark Bay stromatolites and microbial mats (Burns et al, 2004;Papineau et al, 2005;Allen et al, 2009;Goh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These hydrochemical fluctuations together with the hydrodynamical changes typical of tidal environments could alternately promote grain trapping and mat calcification in Leza coarse-grained stromatolites. However, biotic changes (e.g., alternation of mats of differing microbial composition at the stromatolite surface) cannot be ruled out, especially since mats of varied biotic compositions can alternate at the surface of present-day coarse-grained carbonate examples (Bowlin et al, 2012;Jahnert and Collins, 2013).…”
Section: Macroscopic Laminationmentioning
confidence: 99%
“…Modern microbial mats, including laminated lithifying smooth mats, have been reported in the World Heritage listed Shark Bay, Western Australia [17,18]. Previous studies on microbial mats from Hamelin Pool have revealed a high biodiversity in both smooth and pustular mats [19][20][21].…”
Section: Introductionmentioning
confidence: 97%